Conceptual framework and taxonomy of innovation: A case of Malaysia and Thailand public sector - Kruthchon, Thuanthong; Khalil, Samihah (2013)
This paper has two purposes.First, it aims to critically review the conceptual framework of innovation.Scholars view the term innovation with different meanings and this paper discusses several significant concepts of innovation.In doing so, three major taxonomies of innovation will be given focus- product and service, service delivery, and organization innovation.Second, this paper discusses significance, best practice of innovation taxonomy in both private and public sector.Two case studies are reviewed to illustrate innovation initiative in public sector which has taken place in Malaysia and 'Thailand.